Switching the Luminescence between TADF and RTP for Organic D‐A‐D Emitters: The Role of D‐A Connection Modes. Issue 2 (18th December 2022) - Ali, Usman; Han, Guangchao; Yi, Yuanping
Abstract: The impact of the connection modes between donor (D) and acceptor (A) on the luminescence properties is revealed for organic D‐A‐D emitters based on triphenylamine (TPA) and 9, 10‐phenanthroquinone (PAQ). When TPA and PAQ are linked via a single bond, the emitters exhibit small energy difference between the lowest singlet and triplet excited states (∆ E ST ) due to the separated highest occupied molecular orbital (HOMO) and lowest unoccupied molecular orbital (LUMO) distributions, thus featuring thermally activated delayed fluorescence (TADF). Interestingly, for the emitters with TPA and PAQ sharing a benzene ring, the ∆ E ST are significantly increased because of the enhanced overlap between the HOMO and LUMO, which is beneficial to realize room temperature phosphorescence (RTP). Moreover, upon changing the connection from β to γ‐position, high‐lying triplet states can become energetically lower than the lowest singlet excited state, thus affording additional channels to facilitate TADF and RTP. This work sheds some light on controlling of the excited state energy level alignments via modulating the D‐A connection modes to tune molecular emission from TADF to RTP. Abstract : The connection modes between the donor and acceptor units can play a crucial role in controlling the excited state energy level alignments and electronic properties to tune the luminescence from thermally activated delayed fluorescence and room temperature phosphorescence for organic donor–acceptor–donor emitters.